Health seeking behaviour among elderly in Nason Rural Municipality, Manang - Lama, Tasi; Baskota, Swechhya; Gurung, Minani; Poudel, Lisasha; Bhandari, Niroj; Lama, Sonam Dickey (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Health seeking behavior refers to the action taken by the individuals to maintain, attain, and regain good health and to prevent the illness. Despite increasing number of health care delivery system in our country still people are not utilizing health service properly. As the age advances, there is a high chance of having both physical and mental impairment. Thus, the objective of the study was to assess health seeking behavior among elderly and to find-out factors associated with it.Method:  A community-based cross-sectional study was conducted in Nason Rural Municipality of Manang district among 115 elderly aged 60 or above. Semi-structured questionnaire was used for collecting the information. Data was entered and analyzed in SPSS version 23 by using Simple statistical methods. Uni-variate analysis was done and was presented through frequency and percentage whereas, bivariate analysis was done and presented through chi-square test.Result: The main finding of the study showed that that all the participants (100%) were seeking help for health problem in which 90.6% seek  help from Modern medication and 9.4% seek help from Alternative medication. Ethnicity (0.024) and means of transportation (0.023) were only factors which was significantly associated with health seeking behaviorConclusion:  Based on the study findings, most of the respondents had visited Modern health services and only few of respondents had visited Traditional health services. Thus, health seeking behavior among elderly was better than the comparative studies